State bank transformation in Brazil : choices and consequences - Beck, Thorsten, 1967- 1967- (Policy research working paper, 2005)
"The authors analyze the different options-liquidation, federalization, privatization, and restructuring-that the Brazilian state government had for the transformation of state banks under the Programa de Incentivo á Redu袯 do Setor Público Estadual na Atividade Bancária (PROES) in the late 1990s. Specifically, they explore the factors behind the states' choices and the effects of the transformation process on bank performance and efficiency. The authors find that states that were more dependent on federal transfers, whose banks were already under federal intervention and that established development agencies were more likely to relinquish control over their banks and transformation processes. They also find that privatized banks had improved performance, while restructured banks did not. "--World Bank web site